Vegetação de entorno e sua influência sobre insetos praga e parasitoides em cultivos de cana e milho na Guatemala - Mendez, Heisler Alexsander Gomez (2017)
The intensive use of agrochemicals, with low efficiency in pest control, the demand for organic products, among others, has led to the search for alternatives for the management of phytophagous insects, among them the conservation biological control based on the maintainence of enemies through vegetation corridors or strips of attractive plants, which are being studied. The objectives of this work were: a) to evaluate the influence of mexican marigold Tagetes erecta on the richness, abundance and diversity of parasitoids in maize crop and on infestation by the fall armyworm S. frugiperda; b) to evaluate the influence of a vegetation corridor on the richness, abundance and diversity of parasitoids in sugarcane cultivation. For both experiments, yellow traps were used in transects at different distances from the attractive plant or vegetation corridor, to evaluate the dispersion of parasitoid insects to the interior of these crops. The results allowed observing that the floral feature of the T. erecta influenced the richness and abundance of parasitoids, with a decrease gradient inside the culture, as well as reducing infestations of the caterpillar close to the attractive strip. For the case of sugarcane, there was also an influence on the movement of parasitoids to the interior of the crop, with a decrease gradient towards the interior. Species of parasitoids of the main maize and cane pests were collected during the experiments, at different distances from the most diversified regions. Therefore, the use of T. erecta in strips and the maintenance of vegetation corridors are technologies that have great potential for the management of crop pests, being able to attract, conserve and distribute natural enemies to the productive agroecosystem.